Transport and mixing patterns over Central California during the carbonaceous aerosol and radiative effects study (CARES) - J. D. Fast (Atmospheric Chemistry and Physics, 2012)
We describe the synoptic and regional-scale meteorological conditions that affected the transport and mixing of trace gases and aerosols in the vicinity of Sacramento, California during June 2010 when the Carbonaceous Aerosol and Radiative Effects Study (CARES) was conducted. The meteorological measurements collected by various instruments deployed during the campaign and the performance of the chemistry version of the Weather Research and Forecasting model (WRF-Chem) are both discussed. WRF-Chem was run daily during the campaign to forecast the spatial and temporal variation of carbon monoxide emitted from 20 anthropogenic source regions in California to guide aircraft sampling. The model is shown to reproduce the overall circulations and boundary-layer characteristics in the region, although errors in the upslope wind speed and boundary-layer depth contribute to differences in the observed and simulated carbon monoxide. Thermally-driven upslope flows that transported pollutants from Sacramento over the foothills of the Sierra Nevada occurred every afternoon, except during three periods when the passage of mid-tropospheric troughs disrupted the regional-scale flow patterns. The meteorological conditions after the passage of the third trough were the most favorable for photochemistry and likely formation of secondary organic aerosols. Meteorological measurements and model forecasts indicate that the Sacramento pollutant plume was likely transported over a downwind site that collected trace gas and aerosol measurements during 23 time periods; however, direct transport occurred during only eight of these periods. The model also showed that emissions from the San Francisco Bay area transported by intrusions of marine air contributed a large fraction of the carbon monoxide in the vicinity of Sacramento, suggesting that this source likely affects local chemistry. Contributions from other sources of pollutants, such as those in the Sacramento Valley and San Joaquin Valley, were relatively low. Aerosol layering in the free troposphere was observed during the morning by an airborne Lidar. WRF-Chem forecasts showed that mountain venting processes contributed to aged pollutants aloft in the valley atmosphere that are then entrained into the growing boundary layer the subsequent day.